1989
DOI: 10.1139/b89-270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of seedling protection induced by a hypovirulent isolate of Rhizoctonia solani

Abstract: Among several hypovirulent isolates of Rhizoctonia spp. tested, one isolate (No. 521) provided significantly higher protection (76–94%) to radish and cotton seedlings against infection by virulent isoltes of Rhizoctonia spp. and also induced a higher increased plant growth response than the others. The hypovirulent strain did not compete for root exudates. The protected plants were not induced to produce new polyphenols, melanins, more lignins, or phytoalexins. Also they did not produce inhibitors of pectinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The alteration in ROSscavenging enzymes could be a vital process in phytopathogen defense (Gara et al 2003). Non-pathogenic microbial inoculation can heighten the resistance of host plants against their pathogens by an increase of phenolic compounds (Gasoni and Gurfinkel 2009;Sneh et al 1989). In support of this, we found that the phenolic content of R. solani-infected plants was less than that of the controls, but again, B. amyloliquefaciens subsp.…”
Section: Discussionsupporting
confidence: 57%
“…The alteration in ROSscavenging enzymes could be a vital process in phytopathogen defense (Gara et al 2003). Non-pathogenic microbial inoculation can heighten the resistance of host plants against their pathogens by an increase of phenolic compounds (Gasoni and Gurfinkel 2009;Sneh et al 1989). In support of this, we found that the phenolic content of R. solani-infected plants was less than that of the controls, but again, B. amyloliquefaciens subsp.…”
Section: Discussionsupporting
confidence: 57%
“…Today, it is well established that Rhizoctonia is significantly affected by suppressive organisms, but the nature of this biocontrol is still a matter of debate [4]. The finding that hypovirulent isolates of Rhizoctonia can be successfully used for biocontrol purposes, raised also interest in the possible involvement of mycoviruses [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al (2010) showed that a decrease of V. dahliae wilt on potato correlated with an increase in root colonization by non-pathogenic Fusarium equiseti. Sneh et al (1989) reported that the hypovirulent Rhizoctonia sp. isolate 521 provided significant protection on radish against virulent Rhizoctonia strains by densely colonizing the root surface.…”
Section: Competitionmentioning
confidence: 99%